Nanonaringenin and Vitamin E Ameliorate Some Behavioral, Biochemical, and Brain Tissue Alterations Induced by Nicotine in Rats - Mohamed A. Kandeil; Eman T. Mohammed; Rania A. Radi; Fatma Khalil; Abdel-Razik H. Abdel-Razik; Mohamed M. Abdel-Daim; Ghada M. Safwat (Journal of Toxicology)
Nicotine is the major alkaloid present in cigarettes that induces various biochemical and behavioral changes. Nanonaringenin (NNG) and vitamin E are antioxidants that are reported to mitigate serious impairments caused by some toxins and oxidants. Thus, we aimed to investigate the efficacy of NNG, vitamin E, and their combinations to ameliorate behavioral, biochemical, and histological alterations induced by nicotine in rats. Adult male albino rats were randomly grouped into six equal groups (10 rats/group): control, N (nicotine 1 mg/kg b.w./day S/C from 15th to 45th day, 5 days a week), NNG (25 mg/kg b.w./day orally for 45 days), N + NNG, N + E (nicotine + vitamin E 200 mg/kg b.w./day orally), and N + NNG + E (nicotine + NNG + vitamin E at the aforementioned doses). Behavioral tests were conducted on day 15 and 30 postnicotine injection, while memory tests, brain neurotransmitters, antioxidants, and histopathological examination were examined at day 30 only. As a result, nicotine impaired rats’ activity (hypoactivity and hyperactivity) and memory, induced anxiolytic and anxiogenic effects on rats, and altered neurotransmitters (acetylcholinesterase, serotonin, and dopamine), and redox markers (MDA, H2O2, GSH, and catalase) levels in brain homogenates. Thickening and congestion of the meninges and degeneration of the cerebral neurons and glia cells were observed. Cosupplementation with NNG, vitamin E, and their combination with nicotine was beneficial in the alleviation of activity impairments and improved short memory and cognition defects and exploratory behaviors. Our results indicate the antioxidant potential of NNG and vitamin E by modulating redox markers and neurotransmitters in the brain. Thus, data suggest that the prophylactic use of NNG, vitamin E, and/or their combination for (45 days) may have a successful amelioration of the disrupted behavior and cognition and biochemical and histopathological alterations induced by nicotine.